Response of selected cowpea lines to low soil phosphorus and moisture stress conditions at Ukulima Farm in Limpopo Province - Thosago, Setshele Standford (University of Limpopo, 2015)
Cowpea (Vigna unguiculata L. Walp) is an important grain legume grown in many parts of the world mostly by smallholder (SH) farmers. Low soil phosphorus (P) and drought stress are major constraints to legume production and threaten food security. Root architecture is a spatial configuration of the root system which is influenced by moisture status and P uptake. A field experiment was conducted at Ukulima farm near Modimolle in Waterberg district during 2012/13 summer growing season. The treatments comprised of two levels each for soil P (low and high) and moisture status (water stress and well-watered); and eight cowpea genotypes (Tvu 4632, Tvu 6365, Tvu 9848, Tvu 15445, Tvu 16408, Tvu 15143, Oloyin and IT00K-1217). The low P level implied the available P in the soil measured in situ, which was less than 8 mg kg-1 while the high P level entailed fertilization at the rate of 40 kg P ha-1 application to achieve approximately 35 mg P kg-1 of soil . The root traits measured included angle of adventitious and basal roots, number of basal roots, tap root diameters at 5, 10, 15 and 20 cm soil depths; lateral branching densities at depth 5,10 and 15 cm, nodule score, deep score, shallowness score, 3rd order branching density, and 1.5 branching densities at 5 and 10 cm depth. Plant parameters measured were plant height, number of pods per plant, number of seeds per pod, length of the pods, unshelled weight, shelled weight and number of primary and secondary branches. Photosynthetic parameters measured were photosynthetic rate, intercellular CO2 concentration, water conductance, transpiration rate, vapour pressure deficits, sample cell CO2, sample cell H2O and relative humidity in the cell. All treatment factors were combined as split-split plot arrangement fitted into randomized complete block design; with four replicates. Results indicate that the lateral root branching density at 5 and 10 cm differed significantly (P≤0.05) across cowpea genotypes. Genotype showed significant effect on taproot diameter at 10 cm. Moisture status and P level exerted significant effect on cowpea genotypes 15 cm. There were significant differences (P≤0.05) for lateral root branching density observed at 5 and 10 cm depth in P rates x genotype interaction. Statistical analysis showed that P levels and cowpea genotypes had significant effects (P≤0.05) on mean plant height, biomass and highly significantly effects (P≤0.01) on number of branches, days to physiological maturity and mean pod length. The interaction between cowpea genotype and moisture stress condition significantly (P≤0.05) affected hundred (100) seed weight. Cowpea genotype Tvu16408 obtained highest grain yield of 3240 kg ha-1 and lowest was by IT00K1217 which obtained grain yield of 1256 kg ha-1. Results showed that photosynthetic rate, water conductance, transpiration rate, sample cell CO2, sample cell H2O, relative humidity in the cell, intercellular CO2 and vapour pressure deficit differed significantly (P≤0.05) across cowpea genotypes. Soil moisture condition and cowpea genotype exerted significant (P≤0.01) effect on photosynthetic rate, water conductance, transpiration rate, sample cell CO2, sample cell H2O and relative humidity in the cell. Variation in P levels had no significant effect on the measured photosynthetic parameters. Oloyin genotype had the highest photosynthetic rate followed by Tvu 4632 while cowpea genotype Tvu 9848 had the least photosynthetic rate. Interaction of moisture stress and cowpea genotype had a significant effect on intercellular CO2 concentration. Water stress reduced the intercellular CO2 concentration of Oloyin, Tvu 6365 and 4632 but resulted in a significant increase in intercellular CO2 concentration in Tvu 9848 genotype. Results showed that variation in soil P level exerted a significant (P≤0.05) effect on grain tissue P content and uptake, and a highly significant (P≤0.01) difference in P content across the various cowpea genotypes. Moisture stress exerted a significant (P≤0.05) difference on P uptake. The results showed that P levels and cowpea genotype variation exerted significant (P≤0.05) effects on P content, P uptake and nitrogen (N) uptake. Moisture status and cowpea genotype variation exerted significant (P≤0.05) effects on total N and N uptake. Cowpea genotype Tvu 9848 obtained more total N content (4.37%), while the lowest total N content was obtained by cowpea genotype Tvu 15445 with 3035 mg kg-1. The interaction between cowpea genotype and moisture status exerted a significant (P≤0.05) effect on N and P uptake of immature green pods harvested. There is a need to conduct more studies to identify cowpea genotypes, their root architecture and agronomic measures that can do well under xvii drought stress and low soil P conditions. Research needs to be conducted to enhance cowpea productivity under both low soil P and drought stress. Keywords: cowpea genotypes; moisture stress; phosphorus fertilisation; root traits
Thesis (M. Sc.(Agronomy)) -- University of Limpopo, 2015
Keywords: Cowpea genotypes; Moisture stress; Phosphorus fertilization; Root traits; Legumes as food; Cowpea